ANALISA PELAKSANAAN KUALITAS TERHADAP KINERJA PELAYANAN DALAM MEWUJUDKAN KEPUASAN PELANGGAN - Megawati, Adong Hotma (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
Along with the development of technology and information, organizational problems are increasing both in terms of quantity and quality demands of service users. Service quality is an important factor and root that is able to provide satisfaction for customers. So that customers feel satisfied with the services provided The purpose of writing this article is to discuss the influence of service implementation on service performance in realizing customer satisfaction. This research uses library research methods by collecting several journals related to the research title. A total of 20 research journals were used as references in this research. The results of the discussion show that service quality influences service performance in realizing customer satisfaction, service quality influences service performance, service quality influences customer satisfaction, service performance influences customer satisfaction. This article concludes that achieving customer satisfaction and optimal service performance can be done by improving service quality.